EDUKASI PEMANFAATAN INTERNET SEHAT DAN AMAN BAGI SISWA/ SISWI SMKN 12 JAKARTA - Ramadhan, Muhamad Lutfi; Wijonarko, Panji; Hamdala, Marcia Rizky; Zain, Zahra Nasywa; Zalianti, Nabila Reva; Nurulah, Ilyas Yasin; Rumbiak, Almendo Renal Yustus; Sarifudin, Maulana; Widagdo, Kristian Widiono Kusumo (Universitas 17 Agustus 1945 Jakarta, 2024)
The development of IT is currently growing very fast and one of the factors that influence it is the presence of the Internet. The Internet provides various conveniences in accessing information in Realtime, quickly and has become a necessity in everyday social life. One of the segmentations of internet users is teenagers. In this digital era, the lifestyle of teenagers has changed. Teenagers and internet usage are now inseparable and very close to each other. In line with advances the internet and the ease of access to information, so that the negative threat from the internet is very real. It is expected that teenagers can utilize and use the internet more for more positive things. Healthy internet socialization activities have been carried out in various fields, such as secondary education, higher education, and the Business Field. The purpose of this community service activity is themed